Analysis of students interest in the social science program in choosing cross-interests in biology at SMAN 2 Rantau Utara - Putri Iratri Pohan (Priviet Social Sciences Journal, 2023)
This study aims to determine the interest of students in the social science program when selecting the cross-interest in Biology at SMAN 2 Rantau Utara for class XI IIS 2. The research was conducted from February to March 2023. The research method employed is descriptive quantitative. The research design adopted is the One-Group Posttest Only type (a single-class study). The population of this study consisted of all the class XI IIS (cross-interest) students at SMAN 2 Rantau Utara, totaling 89 students. The sampling technique employed was purposive sampling, meaning the sample was selected based on criteria determined by the researcher. Hence, the researcher chose the XI IIS 2 social science program class, comprising 28 students. Data collection in this study was done using a questionnaire, which was distributed directly during the research period. Based on the calculations, the learning interest of students in class XI IIS 2 at SMAN 2 Rantau Utara was found to be 72.46%. This percentage is derived from the responses to the distributed questionnaire, indicating that the learning interest of the students in class XI IIS 2 at SMAN 2 Rantau Utara is categorized as high.